2016
DOI: 10.1186/s12879-016-2048-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and clonal diversity of invasive Staphylococcus aureus in the rural Ashanti Region, Ghana

Abstract: Background Staphylococcus aureus is among the most common pathogens isolated from blood cultures in Ghana; yet the epidemiology of blood infections in rural settings is poorly described. This study aims to investigate antimicrobial susceptibility and clonal diversity of S. aureus causing bloodstream infections in two hospitals in the Ashanti Region, Ghana.MethodsBlood cultures were performed for all febrile patients (≥37.5 °C) on hospital admission. Antibiotic susceptibility testing for S. aureus isolates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
11
23
0
Order By: Relevance
“…Our MSSA corresponded to major clones widespread in Poland and other European countries 19 , 49 , 51 54 . In contrast, different predominant clonal complexes were reported in Africa and Asia, indicating geographical variation 53 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 91%
“…Our MSSA corresponded to major clones widespread in Poland and other European countries 19 , 49 , 51 54 . In contrast, different predominant clonal complexes were reported in Africa and Asia, indicating geographical variation 53 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 91%
“…Perhaps the most significant MRSA studies in Ghana are those that focused on isolates from infections of patients, and there are six of such studies (Table 3). [63][64][65][66][67][68] These studies appear to report wide disparities in MRSA prevalence. Two of the studies by Odonkor et al 63 and Karikari et al 64 reported high MRSA prevalence of 33.6% and 34.8%, respectively, whereas two other studies by Dekker et al, 65 and Opintan and Newman 66 reported low MRSA prevalence of <2%.…”
Section: Mrsa and Diseasementioning
confidence: 97%
“…Since then, several retrospective and prospective studies using human S. aureus isolates/samples were carried out in order to search for mecC -MRSA isolates ( Table 1 and Table 2 ) [ 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…In any case, the mecC -MRSA human prevalence detected in most of the studies was very low. Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ].…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%